Cardiovascular risk and the possibility of its correction in women with premature ovarian insufficiency - A. A. Pozdnyakova; L. A. Marchenko; N. K. Runikhina (Акушерство, гинекология и репродукция, 2019)
Since recently, the association of premature ovarian insufficiency (POI) with an increased risk of mortality and morbidity caused by cardiovascular diseases (CVD) has been extensively discussed in the context of early detection and prevention of CVD in these patients. Aim: to evaluate the relative cardiovascular risk (CV risk) before and after hormone replacement therapy (HRT) in women with POI. Materials and methods. The study included 170 women aged from 18 to 40; among them, 85 women with POI and 85 women with regular periods. We evaluated the usual CV risk factors: smoking habits, arterial blood pressure, total cholesterol (TC), low-density lipoproteins (LDL), high-density lipoproteins; in addition, we determined apolipoprotein B (Apo B), high-sensitivity C-reactive protein (hs-CRP), uric acid, and endotelin-1, as well as the functional markers: the right and left carotid intima-media thickness (CIMT) and the brachial artery flow-mediated dilatation (FMD). The CV risk was calculated using the relative risk SCORE scale before and after HRT lasted for 12 months. Results. In the POI group, there were 3.8 times more women with a moderate CV risk (per the SCORE scale), whereas in the POI-free group, women with a low CV risk dominated. In addition, the levels of CV risk markers were 4-fold higher in patients with POI (high levels of Apo B, hs-CRP and uric acid, increased CIMT bilaterally, decreased FMD in the brachial artery). Cyclic HRT during 12 months contributed to the lipid profile normalization, decrease in TC, LDL and FMD in the brachial artery as well as to the decrease of relative CV risk in general. Conclusion. The estrogen deficiency in patients with POI is an independent factor in the increased relative risk of CVD. The HRT has anti-atherogenic, antiinflammatory, and angioprotective effects, regulates the production of endothelium-dependent factors of vasoconstriction and vasodilation, leading to a reduction in the relative risk of CVD in general.